Protective Effect of Polymethoxyflavones Isolated from Kaempferia parviflora against TNF-α-Induced Human Dermal Fibroblast Damage - Hung Manh Phung; Sullim Lee; Sukyung Hong; Sojung Lee; Kiwon Jung; Ki Sung Kang (Antioxidants, 2021)
Similar to other organs, the skin undergoes a natural aging process. Moreover, constant direct exposure to environmental stresses, including ultraviolet irradiation, causes the signs of skin aging to appear rather early. Reactive oxygen species (ROS) and inflammatory responses accelerate skin damage in extrinsic aging. In this study, we aimed to investigate the skin protective effects of polymethoxyflavones found in Kaempferia parviflora against oxidative stress and inflammation-induced damage in human dermal fibroblasts (HDFs) stimulated by tumor necrosis factor-α (TNF-α). The experimental data identified 5,7,4′ trimethoxyflavone (TMF) as the most potent constituent in preventing TNF-α-induced HDF damage among the tested compounds and it was not only effective in inhibiting matrix metalloproteinase-1 (MMP-1) production but also in stimulating collagen, type I, and alpha 1 (COLIA1) expression. TMF suppressed TNF-α-stimulated generation of ROS and pro-inflammatory mediators, such as cyclooxygenase-2 (COX-2), interleukin (IL)-1β, and IL-6 in HDFs. TMF also inhibited the pathways regulating fibroblast damage, including mitogen-activated protein kinase (MAPK), activator protein 1 (AP-1), and nuclear factor-kappa B (NF-κB). In conclusion, TMF may be a potential agent for preventing skin aging and other dermatological disorders associated with oxidative stress and inflammation.